Comparison of normalization methods for Illumina BeadChip HumanHT-12 v3 - Schmid, Ramona; Baum, Patrick; Ittrich, Carina; Fundel-Clemens, Katrin; Huber, Wolfgang; Brors, Benedikt; Eils, Roland; Weith, Andreas; Mennerich, Detlev; Quast, Karsten (BMC genomics, 2010)
Normalization of microarrays is a standard practice to account for and minimize effects which are not due to the controlled factors in an experiment. There is an overwhelming number of different methods that can be applied, none of which is ideally suited for all experimental designs. Thus, it is important to identify a normalization method appropriate for the experimental setup under consideration that is neither too negligent nor too stringent. Major aim is to derive optimal results from the underlying experiment. Comparisons of different normalization methods have already been conducted, none of which, to our knowledge, comparing more than a handful of methods.
Gesehen am 13.06.2023